Analisis Minat Belajar PAI pada Siswa di SMKS Muhammadiyah 9 Medan - Angga kurniawan; Nurul Zahriani JF (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This research endeavors to scrutinize how keen students are on learning Islamic Religious Education (PAI) at SMKS Muhammadiyah 9 Medan. The impetus for this investigation arises from the noticeable lack of enthusiasm among students when they attend PAI lessons. These lessons are frequently seen as uninteresting, lacking variety, and less stimulating when compared to the vocational subjects they are studying. These circumstances create difficulties for PAI instructors, who must establish a learning environment that not only delivers content but also cultivates real motivation and a genuine passion in the students. A qualitative descriptive method was used for this study, and information was gathered through classroom observations, conversations with instructors and students, and surveys to gain insights into students' views on their educational experiences. The information was analyzed to pinpoint the internal and external elements that affect learning interest. The results show that the students' level of interest in learning is somewhere between moderate and low. Personal drive, study routines, and students' mental preparation are examples of internal variables, whereas teaching strategies, the use of educational resources, and the backing of the school setting and family are examples of external variables. The research emphasizes the necessity for teaching strategies that are relevant, diverse, engaging, and more in line with the requirements of the students, based on these findings. It is hoped that learning PAI will not only improve cognitive comprehension but will also raise awareness of the significance of Islamic principles in daily life.